Memaknai Istilah Antikristus dalam Surat-surat Yohanes dan Penerapannya dalam Menghadapi Ajaran Palsu pada Masa Kini - Arnolis Ratupaira (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
The letters of John are significant in understanding the concept of the antichrist, as they reveal how the antichrist refers to false teachers, including liars and deceivers. These individuals have separated themselves from the original group of believers and have embraced false teachings. This study addresses the challenge believers face in interpreting the term "antichrist" in the letters of John and the lack of understanding among believers regarding how to apply biblical steps in confronting false teachers and teachings today. The purpose of this research is to provide an understanding of the term "antichrist" in the letters of John and to outline the steps believers can take in confronting false teachings today. The method used in this research is a library study with contextual Biblical analysis to produce a comprehensive and systematic scientific study. The conclusion of this research is that the term "antichrist" refers to false teachers and teachings or anything that seeks to replace Christ. Therefore, it is crucial for believers to cultivate a strong spiritual life, engage in dialogue, and practice apologetics to confront false teachers and teachings in today's context. The conclusion of the research indicates that the term “antichrist” refers to individuals who do not truly believe in Christ, as well as to liars and deceivers. Steps necessary for confronting false teachers and their doctrines—such as maintaining a high-quality spiritual life, engaging in dialogue, and applying apologetics—are deemed essential for the church today. Pentingnya memaknai istilah “antikristus” dalam surat-surat Yohanes, karena antikristus yang dimaksud Yohanes adalah merujuk kepada para guru palsu. Para guru palsu ini meliputi antikristus, Pendusta, dan Penyesat. Mereka adalah orang-orang yang mengundurkan diri dari kelompok jemaat mula-mula dan mengajarkan ajaran palsu. Masalah yang menjadi kajian dalam penelitian ini adalah kesulitan orang percaya dalam memaknai istilah antikristus dalam surat-surat Yohanes dan minimnya orang percaya memahami dan menerapkan Langkah-langkah berdasarkan Alkitab untuk menghadapi para guru palsu dan ajaran palsu masa kini. Tujuan penelitian ini adalah untuk menemukan dan memberikan pemahaman tentang pemaknaan istilah antikristus dalam surat-surat Yohanes dan Langkah-langkah orang percaya dalam menghadapi ajaran palsu masa kini. Metode yang digunakan dalam penelitian ini adalah metode studi Pustaka dengan pendekatan Biblikal kontekstual guna mendapatkan hasil kajian secara ilmiah yang komprehensif dan sistematis. Kesimpulan dari penelitian tentang pemaknaan istilah antikristus yaitu orang yang tidak sungguh-sungguh percaya Kristus, pendusta, dan penyesat. Dan langkah-langkah yang perlu dipahami untuk menghadapi para guru palsu dan ajaran-ajarannya, yaitu memiliki kehidupan rohani yang berkualitas, berdialog dan berapologetika, penting diterapkan pada gereja masa kini.